The Role of E-Cadherin in Maintaining the Barrier Function of Corneal Epithelium after Treatment with Cultured Autologous Oral Mucosa Epithelial Cell Sheet Grafts for Limbal Stem Deficiency - Fawzia Bardag-Gorce; Richard H. Hoft; Andrew Wood; Joan Oliva; Hope Niihara; Andrew Makalinao; Jacquelyn Thropay; Derek Pan; Imara Meepe; Kumar Tiger; Julio Garcia; Amanda Laporte; et al. (Journal of Ophthalmology)
The role of E-cadherin in epithelial barrier function of cultured autologous oral mucosa epithelial cell sheet (CAOMECS) grafts was examined. CAOMECS were cultured on a temperature-responsive surface and grafted onto rabbit corneas with Limbal Stem Cell Deficiency (LSCD). E-cadherin levels were significantly higher in CAOMECS compared to normal and LSCD epithelium. Beta-catenin colocalized with E-cadherin in CAOMECS cell membranes while phosphorylated beta-catenin was significantly increased. ZO-1, occludin, and Cnx43 were also strongly expressed in CAOMECS. E-cadherin and beta-catenin localization at the cell membrane was reduced in LSCD corneas, while CAOMECS-grafted corneas showed a restoration of E-cadherin and beta-catenin expression. LSCD corneas did not show continuous staining for ZO-1 or for Cnx43, while CAOMECS-grafted corneas showed a positive expression of ZO-1 and Cnx43. Cascade Blue® hydrazide did not pass through CAOMECS. Because E-cadherin interactions are calcium-dependent, EGTA was used to chelate calcium and disrupt cell adhesion. EGTA-treated CAOMECS completely detached from cell culture surface, and E-cadherin levels were significantly decreased. In conclusion, E cadherin high expression contributed to CAOMECS tight and gap junction protein recruitment at the cell membrane, thus promoting cellular adhesion and a functional barrier to protect the ocular surface.